Stringing Together Diversity: Exploring Indonesian Culture Through The TRI N Integrated Indonesian Traditional House (Puradi) Puzzle (Niteni, Nirokke, Nambahi) - Pri Hastuti Komarul; Insanul Qisti Bariyah; Heri Maria Zulfiati; Sutrisna Wibawa (Green Publisher Indonesia, 2025)
This study aims to explore the effectiveness of the project